PENGARUH KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 – 2022 - Salsabila, Anisa Qosidatu; Prijanto, Budi (Jurnal Nusa Akuntansi, 2025)
This research aims to analyze the influence of environmental performance on financial performance, the influence of environmental performance on Corporate Social Responsibility (CSR), the influence of Corporate Social Responsibility (CSR) on financial performance and the influence of environmental performance on financial performance through Corporate Social Responsibility (CSR). The population used in this research is energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. The sampling technique used is the purposive sampling method, with the sample results obtained as many as 11 companies that meet the criteria and a total of 55 data sets. The data analysis techniques used are simple linear regression analysis, multiple linear regression analysis, and Sobel test with the help of SPSS 29 software. The research results show that the environmental performance variable has a significant effect on the financial performance variable, the environmental performance variable has a significant effect on the Corporate Social Responsibility (CSR) variable, the Corporate Social Responsibility (CSR) variable does not have a significant effect on the financial performance variable, and the Corporate Social Responsibility variable (CSR) indirectly does not have a significant effect in mediating environmental performance variables and financial performance variables.